SCREENING FOR OVARIAN CANCER: REALITY AND PROSPECTS. REVIEW OF THE LITERATURE - E. V. Gerfanova; L. A. Ashrafyan; I. B. Antonova; O. I. Aleshikova; S. V. Ivashina (ABV-press, 2015)
A review article presents the modern methods of screening and early diagnosis of primary ovarian cancer (OC). This issue is still relevant in view of the continuing upward trend in incidence rate ratios along with a slight decrease in mortality and 5-year survival rate, as well as the lack of clear definition of the concept of pathogenesis. The diagnostic value of tumor markers and their potential, advantages and disadvantages are discussed. In light of this the need becomes evident for combination of tumor markers with radiological method of imaging, such as transvaginal sonography as the most affordable, safe and multi-reproducible method enabling to most accurately determine the nature of the process, its nosology belonging, as well as to carry out the required dynamic monitoring within a short time. More advanced imaging techniques such as computer tomography or magnetic resonance imaging proved too expensive for widespread use in view of their limited sensitivity and specificity. Attempt to assess the performance of marker screening on the base of CA-125 in groups, divided by clinical and pathogenic way of OC development also proved to be ineffective. Currently, none of the presented algorithms can meet the criteria of economic efficiency, even in the most developed countries. In view of the above, possible options to enhance their performance by developing reliable multimarker panels, the use of ultrasound color power doppler mapping, and others are considered. In addition, the feasibility and application prospects of ultrasound elastometry, mass-spectrometry, IVDMIA tests, OVA dx-test as part of screening programs are discussed. The data of recent studies on the direct comparison of diagnostic tests is given. The importance of genetic counseling for persons at high risk of cancer development process is noted. In case of mutation detection in the BRCA1, BRCA2 genes, in some countries a wide range of preventive activities is recommended: from regular «targeted» preventive examinations to the prophylactic oophorectomy and mastectomy. Increased survival rate of patients with OC is the main aim of all scientific research.